A Novel Chaotic Ciphering System for Color Digital Images - FARAOUN, K. M. (Malaysian Journal of Computer Science, 2009)
Chaotic cryptology has been widely investigated recently. A common feature in the most recent developments of chaotic cryptosystems is the use of a single dynamical map in the encoding–decoding process. The main objective of this paper is to provide a set of chaotic systems instead of a single one for cryptography. We propose a symmetric key stream cipher algorithm in which multiple one-dimensional chaotic maps are used instead of a one-dimensional chaotic map. We demonstrate that the produced key streams have good statistical properties, such as uniform distribution and very height sensitivity to initial conditions. The proposed approaches are applied for color images cryptography. Analysis of the results demonstrates the robustness of the algorithm against different cryptanalysis attacks. The proposed cryptosystem is shown to be robust against brute force attack, plain text attack and differential attacks, and can achieve a ciphering rate of 40Mb/S.